2012
DOI: 10.4238/2012.september.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci for blast resistance in BC2F3 and BC2F5 advanced backcross families of rice

Abstract: ABSTRACT. Advanced backcross families derived from Oryza sativa cv MR219/O. rufipogon IRGC105491 were utilized for identification of quantitative trait loci (QTL) for blast resistance using simple sequence repeat markers. Two hundred and sixty-one BC 2 F 3 families were used to construct a linkage map, using 87 markers, which covered 2375.2 cM of 12 rice chromosomes, with a mean density of 27.3 cM. The families were evaluated in a greenhouse for resistance to blast disease caused by pathotypes P7.2 and P5.0 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…With the growing population, the demand made on the supply of rice is high. Therefore, breeding programs are directed towards increasing yield in response to both biotic and abiotic stresses [14,15]. One such stress that affects yield is drought.…”
Section: Introductionmentioning
confidence: 99%
“…With the growing population, the demand made on the supply of rice is high. Therefore, breeding programs are directed towards increasing yield in response to both biotic and abiotic stresses [14,15]. One such stress that affects yield is drought.…”
Section: Introductionmentioning
confidence: 99%
“…Several inheritance studies have been reported that have used Japanese races (e.g., Kiyosawa, 1981;He and Shen, 1990). In Malaysia, inheritance studies have been performed using local isolates (Rahim et al, 2012), including BC 2 F 3 and BC 2 F 5 advanced backcrosses (Oryza rufipogon x MR219). Four dominant genes at different loci were identified against the most virulent pathotype of M. oryzae Tanweer et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified blast QTL from susceptible lines under greenhouse conditions (Xu et al, 2004; Lopez‐Gerena, 2006). The resistance QTL qBLR10‐1 and qBLR10‐2 colocalized with qBL10.1 (Rahim et al, 2012) and OsMPK6 (Hu et al, 2008), suggesting that they may be involved in similar blast‐resistant responses. It is also possible that differences in resistance QTL detected in the greenhouse was a result of confounding environmental effects, including the presence of different blast races in the field.…”
Section: Discussionmentioning
confidence: 98%